METHODS AND TOOLS FOR MANAGING CONFLICT WITHIN TRANSPORTATION ORGANIZATIONS - Xusanova Nigora Patxullayevna; Mustayeva Guldora Salokhiddinovna (TADQIQOTLAR.UZ, 2024)
Abstract: This article exposition undertakes an in-depth investigation into the methodologies and tools utilized for conflict management within transportation organizations. The study rigorously examines the dynamic terrain of conflict resolution strategies within this sector, elucidating the diverse approaches and instruments employed to cultivate harmonious and effective organizational environments.